Pengaruh Faktor Demografi dan Literasi keuangan dengan Behavior Finance dalam Pengambilan Keputusan Investasi - Siratan, Elkunny Dovir; Setiawan, Temy (Faculty of Economic and Business, 2021)
The investment decision-making process is influenced by various factors, including financial literacy and demographic factors. This research examines the impact of demographic factors and financial literacy with behavioral finance as a mediation on investment decision making. This research using structural equation model (SEM) analysis. The result shows that demographic factors through gender, age, education, income, occupation and experience have an influence and cause a specific behavior in investment decision making. Then the financial literacy factor has an influence in reducing negative behavior. Likewise, demographic factors and financial literacy with behavioral finance as a mediation on investment decisions have a positive influence. The existence of behavior that is manages with planning, financial literacy support, and demographic factors owned by individual investors will create an opportunity for market momentum. Which help maximize profit, better investment and portfolio performance, avoid risks, better investment decision, and forming trading strategies.